2018
DOI: 10.1523/jneurosci.3017-17.2018
|View full text |Cite
|
Sign up to set email alerts
|

NOS3 Inhibition Confers Post-Ischemic Protection to Young and Aging White Matter Integrity by Conserving Mitochondrial Dynamics and Miro-2 Levels

Abstract: White matter (WM) damage following a stroke underlies a majority of the neurological disability that is subsequently observed. Although ischemic injury mechanisms are age-dependent, conserving axonal mitochondria provides consistent post-ischemic protection to young and aging WM. Nitric oxide synthase (NOS) activation is a major cause of oxidative and mitochondrial injury in gray matter during ischemia; therefore, we used a pure WM tract, isolated male mouse optic nerve, to investigate whether NOS inhibition p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 104 publications
2
20
0
Order By: Relevance
“…Also, we found inhibition of eNOS mRNA expression in the hippocampus CA1 zone of 1.5-month-old rats undergoing CPH. This does not contradict the data of other researchers and the ideas about the cascade mechanism of ischemic neurodegeneration, which shows an increase in the expression of iNOS and nNOS [2,6,7,9,11,13,16]. The activity and expression of eNOS may vary with the time and severity of ischemic brain damage.…”
Section: Fig 1 Relative Normalized Expression Of Mrna Of (A) Nnos supporting
confidence: 71%
See 2 more Smart Citations
“…Also, we found inhibition of eNOS mRNA expression in the hippocampus CA1 zone of 1.5-month-old rats undergoing CPH. This does not contradict the data of other researchers and the ideas about the cascade mechanism of ischemic neurodegeneration, which shows an increase in the expression of iNOS and nNOS [2,6,7,9,11,13,16]. The activity and expression of eNOS may vary with the time and severity of ischemic brain damage.…”
Section: Fig 1 Relative Normalized Expression Of Mrna Of (A) Nnos supporting
confidence: 71%
“…Expression of mRNA of the NOS endothelial isoform, according to the literature, demonstrates a contradictory nature. According to the numerous data, eNOS is activated at the beginning of hypoxic exposure, and at chronic oxygen deficiency its synthesis decreases [9,11,13]. Wang H. et al (2009) found that eNOS expression was reduced after OGD reperfusion injury.…”
Section: Fig 1 Relative Normalized Expression Of Mrna Of (A) Nnos mentioning
confidence: 99%
See 1 more Smart Citation
“…Memory function is one of the most vulnerable age-related characteristics (Larrabee and Crook, 1994). Previous reports show that aging results in damage to the white matter and hippocampus (Stahon et al, 2016;Bastian et al, 2018;Bishop and Yankner, 2010). However, it is not clear whether one is damaged to a greater or lesser extent than the other.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these genes such as SH3PXD2A have been previously associated with total WMH and ischemic stroke 16,41 . The NOS3 gene is associated with coronary artery disease, migraine, vascular dysfunction, SVD, and ischemic stroke 29,43,51,52 .…”
Section: Genetic Correlation Analyses Between Dwmh and Pvwmh And Othementioning
confidence: 99%